PERLINDUNGAN HUKUM TERHADAP PEMBELI BERITIKAD BAIK DALAM TRANSAKSI JUAL BELI YANG DIBATALKAN KARENA ADANYA GUGATAN PIHAK KETIGA (STUDI KASUS PUTUSAN NOMOR 800/PDT.G/2013/PN.DPS) - Salim Saputra; Rineke Sara (Fakultas Hukum Universitas Borobudur, 2022)
In life in society, many buying and selling transactions are imperfect, meaning that they have a disability in the legal aspect, whether the object of sale and purchase has not been submitted in a buying and selling transaction or regarding the legality of a person's legality to be declared valid as the right to carry out a sale and purchase transaction, then if there is a lawsuit by a third party in a sale and purchase transaction, how are the legal regulations for legal protection for the rights of buyers with good intentions protected. To discuss this problem, the authors use normative juridical research methods. In the case of Decision Number 800/Pdt.G/2013/PN.Dps., the legal protection given to land buyers with good intentions was not considered by the judge. The judge's considerations were only aimed at the Plaintiff without considering the elements of fulfilling the category of good faith buyers whose rights should also be protected in accordance with existing laws.